Effectiveness of Gambir Solution (Uncaria gambir Roxb) to control Escherichia coli on Broiler Chickens - Melisah Yanty Manullang; Ma`ruf Tafsin; Iskandar Sembiring; Tri Hesti Wahyuni; Hasnudi (Jurnal Peternakan Integratif, 2018)
This study aims to determine the provision of gambir solution (Uncaria gambir Roxb) to the number of E. coli colonies in broiler chickens. The research method used Completely Randomized Design (CRD) with 6 treatments and 3 replications. The treatments consists of P0A= Control without infection; P0B = (0%), P1=(2%), P2 = (4%), P3 = (6%), P4 = Tetracycline antibiotics (0.05%). The results showed addition of gambir solution (Uncaria gambir Roxb) gave significant effect (P<0,05) to amount of E. coli colony in broiler chicken. E. coli colonies total in the treatment phase given average for treatment P0A, P0B, P1, P2, P3, P4, sequentially 6.97, 7.80, 6.88, 6.69, 6.34, 6.91 (CFU Log / g). Addition dose with 2-6% of gambir solution effectively reduced the number of E. coli colonies in broiler chickens. The addition dose of gambir solution 2% was able to compensate tetracycline antibiotics to controlling E. coli in broiler chickens.